Challenges in providing access to health facilities for rural citizens in developing countries - Deris M.S.M.; Mohamed M.A.; Mohamed R.R.; Derahman M.N.; Mamat A.R.; Kadir M.F.A.; Abidin A.F.A. (Seventh Sense Research Group, 2023)
One of the challenges faced by the IT industry is to provide access to medical care for citizens living in rural areas. Rural areas in some non-developed countries may be physically hardly accessible to the outside world. For that, it will be difficult for those who live in such an area to get access to hospital services. Some illnesses that normally need immediate medical care may end up with fatality to the bearer. In light of this, we survey through the possibility of providing such a virtual appointment in replacement of a physical visit to the rural citizen so that doctors and hospitals can reach out to them. As the basic requirement, the area should have internet coverage, whether wired or wireless. For every household to connect to the application, they need to have a smartphone or computer. As a result, we proposed a simple framework for the online doctor application, which should serve the needs of the public. 2021 Seventh Sense Research Group